Perlindungan Hukum terhadap Anak sebagai Korban Tindak Pidana Kekerasan Seksual - Elok Ainur Rohmah; Hilwiyatun Nadiroh (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the harmonization between the Child Protection Act and Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) in strengthening legal protection for child victims of sexual violence in Indonesia. Using a normative juridical method with statutory and conceptual approaches, this research analyzes the shift in the legal paradigm from a perpetrator-oriented retributive model toward a victim-centered restorative justice approach. The findings indicate that the integration of these regulations enhances legal certainty through the expansion of valid evidence, including electronic evidence and expert testimony, as well as the recognition of restitution as an enforceable right of victims. The introduction of the victim fund mechanism further ensures the fulfillment of victims’ material and psychological recovery when perpetrators are unable to provide restitution. This study concludes that regulatory synchronization significantly improves procedural protection and reinforces the state’s responsibility in safeguarding the best interests of child victims.